(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the leather resistance of sheep skin ½ Poll Dorset ½ Santa Inês. Twenty hides were distributed in a completely randomized design, in a 2x2x2 factorial, consisting of two tanning techniques (Trat1=with chromium salts. Trat2=without chromium salts), two leather regions (R1=dorsal; R2=ventral) and two-way leather (S1=longitudinal; S2=transversal). In chrome-tanned leathers, the tensile strength (9.48 KgF) was lower (p<0.05) when compared to chrome-tanned leathers (13.38 KgF). The ventral region (6.13 KgF) showed greater resistance to progressive tearing (p<0.05) in relation to the dorsal region (4.75 KgF) when tanned with chromium salts. For the same variable, the chrome-tanned hides showed higher averages (p<0.05) in both regions (R1=4.75 KgF, R2= 6.13 KgF) when compared to the non-chrome (R1= 3.46 kgF; R2 = 3.64 kgF). The hides, regardless of the technique, showed greater elongation in the transverse direction. With chromium salts, it provides greater tear strength in the ventral region compared to the dorsal region. However, the use of vegetable tannins made it possible to obtain leathers with resistance within the standard required for clothing. Being an alternative to more tanning providing less environmental impact.